Burden of illness and health care resource utilization in adult psychiatric outpatients with attention-deficit/hyperactivity disorder in Europe - Karlsdotter, Kristina; Sobanski, Esther (Current medical research and opinion, 2016)
Objective: To assess the burden of illness and health care resource utilization of adult nonpsychotic psychiatric outpatients with attention-deficit/hyperactivity disorder (ADHD) in Europe.Methods: This was a multicountry, cross-sectional, observational study where unselected routine patients from clinical psychiatric outpatient settings were screened and assessed for ADHD. Patients were evaluated using the Clinical Global Impressions of Severity (CGI-S) scale, the Sheehan Disability Scale (SDS), and the EuroQol-5 Dimensions questionnaire. Data on comorbidities, functional impairment, and health care resource utilization were captured.Results: The study enrolled 2284 patients, of whom 1986 completed the study. The prevalence of ADHD was 17.4%, of whom 46.0% had a previous ADHD diagnosis. Patients with ADHD had a high clinical burden with psychiatric comorbidities, especially depression (43.0%) and anxiety disorders (36.4%). Substance abuse (9.2% vs. 3.4%) and alcohol abuse (10.3% vs. 5.2%) were more common in the ADHD cohort vs. the non-ADHD cohort. Only 11.5% of the patients with ADHD had no other psychiatric disorder. Various measures indicated a significantly poorer level of functioning for patients with ADHD than without ADHD, as indicated by higher scores for CGI-S (3.8 vs. 3.3) and SDS (18.9 vs. 11.6) and higher percentages of debt (35.5% vs. 24.3%) and criminality (13.8% vs. 6.1%). Lastly, the health care resource utilization was considerable and similar between adult psychiatric outpatients diagnosed and not diagnosed with ADHD.Conclusions: Although care was taken when choosing the sites for this study, to make it representative of the general outpatient adult psychiatric population, caution should be advised in generalizing the findings of our study to the general ADHD or psychiatric outpatient population. This was an observational study, thus no inference on causality can be drawn. Having ADHD imposes a considerable health and social burden on patient and health care resource utilization comparable to other chronic psychiatric disorders.
Gesehen am 06.08.2019